Xylanase and β-xylosidase production by Aspergillus ochraceus: new perspectives for the application of wheat straw autohydrolysis liquor - Michelin, Michele (2012)
The xylanase biosynthesis is induced by its substrate—xylan. The high xylan content in some wastes such as wheat residues (wheat bran and wheat straw) makes them accessible and cheap sources of inducers to be mainly applied in great volumes of fermentation, such as those of industrial bioreactors. Thus, in this work, the main proposal was incorporated in the nutrient medium wheat straw particles decomposed to soluble compounds (liquor) through treatment of lignocellulosic materials in autohydrolysis process, as a strategy to increase and undervalue xylanase production by Aspergillus ochraceus. The wheat straw autohydrolysis liquor produced in several conditions was used as a sole carbon source or with wheat bran. The best conditions for xylanase and β-xylosidase production were observed when A. ochraceus was cultivated with 1% wheat bran added of 10% wheat straw liquor (produced after 15 min of hydrothermal treatment) as carbon source. This substrate was more favorable when compared with xylan, wheat bran, and wheat straw autohydrolysis liquor used separately. The application of this substrate mixture in a stirred tank bioreactor indicated the possibility of scaling up the process to commercial production.